STATISTICAL CORRECTION OF A DYNAMIC PILE BEARING CAPACITY FORMULA BASED ON PDA DATA - Angelina, Sherlin; Wijaya, Hendy; Iskandar, Ali; Johan, Agus; Kawanda, Aksan; Purnomo, Daniel Tri (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2025)
The calculation of pile bearing capacity using a dynamic formula is considered a practical approach for evaluating the capacity of foundation piles. However, its results are often questioned when compared to the CAPWAP analysis outcomes derived from PDA testing. This study aims to assess the accuracy of the dynamic formula, develop a correction model using a statistical approach in the form MLR, and evaluate the effectiveness of the resulting correction model in predicting pile bearing capacity. A total of 84 pile datasets were utilized in this research, comprising various pile dimensions and PDA-derived parameters, including the maximum energy transferred to the pile (EMX), permanent pile settlement (S = DFN), and elastic settlement (C = DMX – DFN). The analysis results indicated that the dynamic formula could be corrected using the MLR approach. The correction model produced multiplier coefficients of 1.09 for parameter S and 0.67 for parameter C, with a coefficient of determination of 0.96 and a MAPE value of 19.21%, which represents the average deviation of the predicted results from the actual values and falls into the accurate category based on Lewis’ classification. The model is deemed sufficiently reliable for use as an alternative method in the preliminary evaluation of pile bearing capacity. Abstrak Perhitungan daya dukung tiang menggunakan formula dinamik merupakan pendekatan praktis dalam mengevaluasi kapasitas tiang fondasi. Namun, hasil perhitungannya kerap diragukan jika dibandingkan dengan hasil analisis CAPWAP dari uji PDA. Penelitian ini bertujuan untuk mengevaluasi akurasi formula dinamik, mengembangkan model koreksi dengan pendekatan statistik berupa MLR, serta menilai efektivitas model koreksi yang dihasilkan dalam memprediksi daya dukung tiang. Pada penelitian ini digunakan 84 data tiang dengan variasi dimensi tiang dan parameter dari uji PDA yang berupa energi maksimum yang tertransfer ke tiang (EMX), penurunan permanen tiang (S = DFN), dan penurunan elastis tiang (C = DMX – DFN). Hasil analisis menunjukkan bahwa formula dinamik dapat dikoreksi melalui pendekatan MLR. Model koreksi menghasilkan koefisien pengali untuk parameter S sebesar 1,09 dan C sebesar 0,67, serta memiliki koefisien determinasi sebesar 0,96 dan nilai MAPE yang menunjukkan rata-rata deviasi hasil prediksi terhadap aktual sebesar 19,21%, yang termasuk dalam kategori akurat menurut klasifikasi Lewis. Model ini dinilai cukup andal untuk digunakan sebagai pendekatan alternatif dalam tahap evaluasi awal daya dukung tiang.